Effect of one minimum alveolar concentration sevoflurane with and without fentanyl on hemodynamic response to laryngoscopy and tracheal intubation - Anwar Hoda; Fauzia A Khan (Wolters Kluwer Medknow Publications, 2011)
Background : Drug combinations can be used for optimum obtundation of the hemodynamic response to tracheal intubation. The objective of this trial was to compare the hemodynamic response to laryngoscopy and tracheal intubation after administration of 2 μg/kg fentanyl bolus or a placebo with 2% end tidal sevoflurane at induction of anesthesia. Materials and Methods : A total of 70 surgical patients of either gender, age 18-45 years were selected for this double blind, randomized, placebo controlled trial, with 35 in each group. All patients received a standardized induction with thiopentone, atracurium, and an end tidal concentration of 1 minimum alveolar concentration (MAC) sevoflurane. Heart rate and noninvasive blood pressure were compared to the baseline post induction and for seven minutes post intubation. Some adverse events were noted. Results : The maximum heart rate response was significantly less in the sevoflurane fentanyl group (15% vs. 22%). Significant difference between groups was observed in the systolic blood pressure at six minutes post intubation. Hemodynamic adverse events recorded were similar. Conclusion : Addition of 2 μg fentanyl bolus to 1 MAC sevoflurane anesthesia at induction attenuated the hemodynamic response to a maximum of 15% above baseline values.